Lee is trapped, and must be taken : eleven fateful days after Gettysburg: July 4 to July 14, 1863 - Ryan, Thomas J., 1934-; Schaus, Richard R. (Savas Beatie, 2019)
"The objective of this study is to examine Maj. Gen. George G. Meade's strategy and tactics during the eleven days, July 4 to 14, 1863, following the Battle of Gettysburg in response to President Abraham Lincoln who envisaged that the Confederate rebellion would be brought to an end if Meade's Army of the Potomac pursued and crushed Gen. Robert E. Lee's retreating Army of Northern Virginia before it could reach safety across the Potomac River"--